How educational technology innovates distance learning during pandemic crisis in remote areas in Indonesia? - Rayuwati, Rayuwati (International research journal of management, IT and social sciences, 2020)
This study presents the results of a review of seven international publications that discuss how technology can innovate distance learning during a pandemic crisis in remote areas in Indonesia. It cannot be denied that technology services are quite large in helping the learning of the nation's children all over Indonesia. However, we should cool off on educational researchers' findings, especially technology-based learning innovations, which are now increasingly being used in all business and educational activities of the younger generation. We have conducted a review of various literature. Then we continue with a review of ten publications on the role and impact of technology applications on the sustainability of learning in areas where internet networks are still tricky issues. To prove the claim, we conducted a qualitative analysis in a phenomenological and in-depth understanding to ensure that our findings were based on validity and reliability.